Design and performance evaluation of Windows and Linux platform applicable in a virtual architectural walkthrough - Thubaasini, Prabhakaran (Universiti Malaysia Perlis, 2011)
This research describes the design of a virtual architectural walkthrough application, developed and run on two different platforms; Windows and Linux operating system. Both platforms are then compared in order to measure and evaluate the performance of each platform used to build the virtual architectural walkthrough. The decision on which platform performs best is difficult to answer without actual facts and data. Therefore, this research is an attempt to quantify the relative merits of the Windows and Linux operating systems as an underlying platform for a virtual architectural walkthrough and to experimentally determine, which either of the two demonstrates superiority for this task. This is to make sure that the base in which the particular application is run at has sufficient help at its maximum performance. This research is also important to show which operating system has better capabilities, speed and ample of memory to sustain a virtual reality application. In pursuit of this goal, several experiments are detailed and recorded, in which key criteria are compared between the two operating systems. The performance of each platform is measured based on four main key criteria’s which is frame rate, image quality, CPU usage and memory usage. From the overall experiment, results indicate that the frame rate and CPU usage is much better in Linux compared to Windows platform. Meanwhile the memory usage reading shows otherwise. As for the image quality, Linux has much better capabilities in maintaining its image quality compared to Windows platform. Using completely identical hardware, one operating system stood out from the other as a foundation for a virtual architectural walkthrough application. While Linux did not completely dominate every test, it should be obvious that the vast majority of the results strongly favor a virtual architectural walkthrough on Linux rather than Windows in terms of its performance. Besides having an excellent performance, Linux has the advantage of being open source. It has the capability of minimizing the budget of development and lower the cost of infrastructure which is good for all VR developers since the cost of development is far too expensive when it comes to proprietary software.